Penerapan DGBL Dalam Game Edukasi Pengenalan Kaulinan Tradisional Sunda Berbasis Android - Rahayu, Sri; Tresnawati, Dewi; Fatmalasari, Intan Sri (Jurnal Algoritma, 2025)
Traditional games in West Java known as “kaulinan barudak” or “kaulinan barudak baheula” have many moral themes that convey extraordinary local wisdom, and serve as a mirror of the ideals that define people's lives. Due to the reduced availability of play areas and the lack of socialization regarding the importance of traditional games, and fewer and fewer children are involved in these activities and some do not even know about them. So the purpose of making this android application is to create an application educational game that is expected to be a means to help children get to know traditional games in West Java, besides that this application is also expected to be an important means in an effort to preserve this valuable cultural heritage from threats posed by the impact of modern culture today. This application was developed using the DGBL-ID methodology (Digital Game Based Learning-Instructional Design),